The role of the Russian language in the determination of Kazakh students - Baimurzina, Ainur A.; Almagul A. Khabiyeva, Aigul B. Amirbekova,; Abitova, Gaukhar O. (Opción, 2019)
The article examines the role of the Russian language in the language identity of Kazakhstan students, in the context of the country’s ethnolinguistic diversity and the continued dominance of the Russian language. The data collection method consisted of a mass survey and the data were analyzed statistically. The findings demonstrate that proficiency in specific languages and language choice are factors of socialization of Kazakh university students. In conclusion, the government of multinational and multi-confessional Kazakhstan should maintain and develop the existing balanced language policy: to develop and support all languages of the peoples of Kazakhstan along with the state language.